Pemberdayaan Keluarga Dalam Asuhan Keperawatan Pasien Kanker Melalui Edukasi Perawatan Nyeri Dan Dukungan Psikososial - Lela Nurlela; Sukma Ayu Candra Kirana; Rahmat Pannyiwi; Markus Wibowo; Arnes Yuli Vandika (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Cancer is one of the leading causes of death in Indonesia, requiring comprehensive management and strong family involvement. Families play a vital role in providing both physical care and psychosocial support to improve the quality of life of cancer patients. This community service program aimed to empower families in performing pain management and psychosocial support for cancer patients at home. The methods included interactive lectures, group discussions, demonstrations of simple pain management techniques, and psychosocial counseling. The activity was carried out in Puskesmas X, City Y, involving 25 family members of cancer patients. Evaluation was conducted using pre-test and post-test questionnaires as well as participant observation. The results showed an 80% increase in family knowledge regarding pain management and emotional support for cancer patients. This activity successfully empowered families to provide holistic nursing care addressing physical, emotional, and spiritual needs. It is recommended that similar programs be continued to strengthen community-based palliative care initiatives.